2012
DOI: 10.1017/s1368980012005083
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to avoiding fast-food consumption in an environment supportive of unhealthy eating

Abstract: Objective: To investigate factors (ability, motivation and the environment) that act as barriers to limiting fast-food consumption in women who live in an environment that is supportive of poor eating habits. Design: Cross-sectional study using self-reports of individual-level data and objectively measured environmental data. Multilevel logistic regression was used to assess factors associated with frequency of fast-food consumption. Setting: Socio-economically disadvantaged areas in metropolitan Melbourne, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(62 reference statements)
0
20
0
1
Order By: Relevance
“…These authors found that students who assign more importance to food for their well-being have healthier eating habits. In this regard, Thornton et al [ 70 ] suggested that healthy behaviors are influenced by an individual’s ability to make healthy behavior choices and his/her motivation to do so.…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that students who assign more importance to food for their well-being have healthier eating habits. In this regard, Thornton et al [ 70 ] suggested that healthy behaviors are influenced by an individual’s ability to make healthy behavior choices and his/her motivation to do so.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Few studies have investigated the diet barriers perceived by underserved adults with type 2 diabetes and all glycemic control levels using validated instruments. 7 , 14 , 15 None of these studies mentioned any attempt to report diet barriers perceived by patients with poor glycemic control via subgroup analysis. The needs and characteristics of patients with poorly controlled diabetes thereby remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, although consumers are willing to consume healthy foods the shopping environment often does not support them to do so ( Cameron et al, 2013 , Thornton et al, 2012 , Thornton et al, 2013 ). Therefore, regulatory policies which discourage the sale of EDNP products are also required ( Nederkoorn et al, 2011 , Moodie et al, 2013 , Pomeranz and Brownell, 2011 ).…”
Section: Discussionmentioning
confidence: 99%